Unlocking Vocabulary: The Role of Card Sort Learning in Junior High School - Al-afRondi, Nur Ainiyah; Reftyawati, Dian; Nawawi, M. (LinguaEducare: Journal of English and Linguistic Studies, 2025)
In acquiring English, vocabulary is the fundamental element of language mastery.  Competence and expertise in English are defined by knowledge of language.  Consequently, vocabulary acquisition is crucial for enhancing students' English language proficiency as both a foreign and second language. Implementing instructional strategies that resonate with students' learning preferences is a means to enhance their English language acquisition. One effective technique is the card sort learning approach.  This study aimed to determine the substantial impact of the Card Sort learning method on the vocabulary of seventh-grade students’ at MTs Nurul Hidayah Al-amin.  This study used a quasi-experimental design. The research population comprised the seventh-grade students of MTs Nurul Hidayah Al-amin, totaling 185 individuals.  The sample comprised 62 students selected from two classes: VII A as the experimental group and VII B as the control group.  The data collection method employed pre-test and post-test assessments. The instrument employed a test concentrating on verbs, pronouns, and nouns.  The data analysis employed content validity, construct validity, item validity, and instrument reliability.  Following the hypothetical test, the data analysis conducted via SPSS revealed that the significance (P-value) was less than 0.001, indicating that the significance (P-value) was lower than the significance level α = 0.05.  The study concluded that the card sort learning approach significantly influenced vocabulary mastering among seventh-grade students at Mts Nurul Hidayah Al-Amin.